(untitled) (Research, Society and Development, 2021)
The paper intends to reveal the work activity of truck drivers in order to understand how the organization of work impacts on the possibility of regularization of workers. The theoretical contribution of Ergonomics and Ergology was used in a cross-sectional descriptive study, developed in three stages: application of questionnaire, declared semi-structured and a cross self-confrontation, by remote way. The results show that there is an absence/deficiency in the management of health and safety at work, which is complex because it involves several companies for which drivers provide services. It is necessary to work on this management in all sectors, create a field of regulation for the driver, who works under the pressure of production, with excessive working hours, difficult for loading and unloading, and it is necessary to offer adequate support and better working conditions, with efficient logistics and adequate service, in order to avoid the risk of illness.